O impacto do Design with Intent nos comportamentos das sociedades contemporâneas - Marchi, Caio Favero (2013)
The object of this study is one of the patterns (Surveillance) of the Security Lens of that which researchers from Brunel University have called Design with Intent (DwI). Based on the question suggested by the object of the study itself (What would happen if citizens knew, or at least believed, that their behavior is being seen or monitored by people in positions of power or authority?) and in the dissemination, more patent every day, of surveillance and control devices in the major metropolises of the world, as is the case of São Paulo, the question that will guide us is: to which extent does the pattern Surveillance, a development of the Security Lens of DwI, incite social behaviors? With the purpose of answering this question and to prove the hypotheses that this method standardizes social behaviors and that it acts, moreover, as a control device of contemporary societies, this study will make use of a hybrid methodology, composed of bibliographic research, documental research and unstructured and undirected interviews. The theoretical frame of reference of the bibliographic research will include Castel (2005) and Bauman (2009) to present the issue of fear and insecurity in large cities; Vaz (2004; 2005; 2006), Kellner (2001) and Wainberg (2005) to clarify the contribution of mass media in the construction of the image of urban violence; Foucault (1997; 2008), Deleuze (2010), Hardt (2000), Rose (1999) and Costa (2004) to elaborate an overview of the transformations and characteristics of the different societal models; Lockton, Harrison and Stanton (2011) to introduce and deepen the debates on the importance of DwI; and Norris and Armstrong (199), Bruno (2010) and Kanashiro (2010) to broach the topic of surveillance and the development of its technological devices (CCTV). The documental research will collect information on violence and fear in the capital of the state of São Paulo from magazines, newspapers and television reports. Finally, we will carry out interviews with the supervisor of the Video Monitoring Center of the São Paulo State Military Police and with the captain of the Batallion that holds the Operation Center of the São Paulo State Military Police (COPOM). These interviews will attempt to extract from primary sources data and information that illustrate some passages of the text in order to allow us to draw a conclusion about the matter in a consistent manner